Fluorine-free weak acid collector and preparation method and application thereof
Patent Information
- Application Number
- CN202611043573.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-14
- Publication Date
- 2026-10-16
AI Technical Summary
尽管氢氟酸活化法与强酸性浮选法是当前工业上实现长石-石英综合回收的主流技术,可有效实现二者的选择性分离,但两类方法均存在设备腐蚀、环境污染及产品品质受限等问题
[0026] 1. This invention addresses the problems of selective separation of quartz and feldspar in tailings, which are difficult in existing technologies and require activation with strong acids and hydrofluoric acid. The fluorine-free weak acid collector is a liquid product prepared by dissolving quaternary ammonium salt, straight-chain fatty alcohol, chloroacetic acid, and sodium trimetaphosphate. The quaternary ammonium salt and straight-chain fatty alcohol are in equal proportions and are both effective active ingredients for collection. Chloroacetic acid and sodium trimetaphosphate are performance-adjusting ingredients. The resulting collector is a water-soluble liquid agent with low-temperature resistance, easy dispersibility, and non-toxicity. The fluorine-free weak acid collector can be used for flotation in weakly acidic slurry environments with a pH of 3.5-5 without the need for other auxiliary reagents. It is suitable for various tailings containing feldspar and quartz, exhibiting excellent selective enrichment characteristics while reducing the risks of equipment corrosion and environmental pollution.
Smart Images

Figure SMS_5 
Figure SMS_6
Abstract
Description
Technical Field
[0001] This invention relates to the field of mineral processing reagents. More specifically, this invention relates to a fluorine-free weak acid collector, its preparation method, and its application. Background Technology
[0002] Tailings from the flotation of lithium mica and the beneficiation of iron ore are usually rich in feldspar and quartz. In some tailings, the mineral content of quartz and feldspar exceeds 95%. If the efficient separation and enrichment of these two minerals can be achieved, the tailings can be transformed into high-value quartz and feldspar products, which can be used as high-quality raw materials for the production of ceramics and glass, thus fundamentally realizing the high-value utilization of tailings.
[0003] The flotation separation of feldspar and quartz mainly includes hydrofluoric acid activation and strong acid flotation. Both methods utilize cationic collectors such as dodecylamine under hydrofluoric acid activation or acidic conditions to selectively float feldspar, thereby achieving separation. Although hydrofluoric acid activation and strong acid flotation are currently the mainstream technologies in industry for the comprehensive recovery of feldspar and quartz, effectively achieving selective separation, both methods suffer from problems such as equipment corrosion, environmental pollution, and limitations in product quality. Summary of the Invention
[0004] The purpose of this invention is to provide a fluorine-free weak acid collector, its preparation method, and its application. This collector can separate feldspar and quartz under fluorine-free weak acid conditions and can be used for the green and efficient separation of feldspar and quartz in tailings rich in quartz and feldspar, such as lepidolite flotation tailings, iron tailings, and copper tailings.
[0005] To achieve these objectives and other advantages according to the present invention, a fluorine-free weak acid collector is provided, comprising the following components in parts by weight:
[0006] 3-7 parts of quaternary ammonium salt, 3-7 parts of straight-chain fatty alcohol, 1-3 parts of chloroacetic acid, and 6-14 parts of sodium trimetaphosphate.
[0007] Furthermore, in the aforementioned fluorine-free weak acid collector, the carbon chain length of the quaternary ammonium salt is C10-C18.
[0008] Furthermore, in the aforementioned fluorine-free weak acid collector, the carbon chain length of the straight-chain fatty alcohol is C8-C12.
[0009] The present invention also provides a method for preparing the fluorine-free weak acid collector according to any one of the above claims, comprising the following steps:
[0010] S1. Mix 3-7 parts by weight of quaternary ammonium salt and 3-7 parts by weight of straight-chain fatty alcohol, and then heat to 50-70℃;
[0011] S2. After the mixture obtained in S1 has melted, add 1-3 parts by weight of chloroacetic acid and 8-20 parts by weight of deionized water, and stir the mixture at 50-70°C for 30-60 minutes.
[0012] S3. After the mixture obtained in S2 has reacted completely, add 6-14 parts by weight of sodium trimetaphosphate and mix well to obtain the collector stock solution.
[0013] S4. Add deionized water to dilute the collector stock solution obtained in S3 to obtain the fluorine-free weak acid collector.
[0014] Furthermore, in the preparation method of the fluorine-free weak acid collector, the concentration of the original collector solution in the diluted fluorine-free weak acid collector in S4 is 2-10%.
[0015] The present invention also provides a feldspar-quartz flotation separation method, using the fluorine-free weak acid collector described in any of the above-mentioned methods.
[0016] Furthermore, the feldspar-quartz flotation separation method includes the following steps:
[0017] Step 1: Take tailings with a quartz and feldspar mineral content of more than 95%, grind them until the proportion of particles with a particle size of less than 0.074mm is 40-90%, and then add water to adjust to obtain a slurry with a mass concentration of 25-40%.
[0018] Step 2: Add hydrochloric acid or sulfuric acid to the slurry obtained in Step 1 to adjust its pH to 3.5-5;
[0019] Step 3: Using the fluorine-free weak acid collector, add it to the slurry treated in Step 2 for flotation roughing to obtain froth product and underflow product. The flotation temperature is 15-40℃.
[0020] Step 4: Using the fluorine-free weak acid collector, the underflow product obtained in Step 3 is subjected to multiple flotation cleaning processes. The pH of the pulp is maintained at 3.5-5 during the flotation cleaning process, and the time for each flotation cleaning is 2-3 minutes. The froth product generated by the flotation cleaning is mixed into the froth product obtained in Step 3.
[0021] Step 5: Filter and dry the underflow product after flotation and the final foam product separately to obtain quartz product and feldspar product respectively.
[0022] Furthermore, in the aforementioned feldspar-quartz flotation separation method, the tailings in step one are one or any combination of lithium mica tailings, iron ore tailings, copper ore tailings, and phosphate ore tailings.
[0023] Furthermore, in the aforementioned feldspar-quartz flotation separation method, the collector consumption during the first flotation cleaning in step four is 50% of the collector consumption during the roughing flotation in step three, and the collector consumption during each subsequent flotation cleaning is 50% of the collector consumption during the previous flotation cleaning.
[0024] Furthermore, in the aforementioned feldspar-quartz flotation separation method, the collector consumption during the roughing flotation in step three is 1000-3000 g / t.
[0025] The beneficial effects of this invention are:
[0026] 1. This invention addresses the problems of selective separation of quartz and feldspar in tailings, which are difficult in existing technologies and require activation with strong acids and hydrofluoric acid. The fluorine-free weak acid collector is a liquid product prepared by dissolving quaternary ammonium salt, straight-chain fatty alcohol, chloroacetic acid, and sodium trimetaphosphate. The quaternary ammonium salt and straight-chain fatty alcohol are in equal proportions and are both effective active ingredients for collection. Chloroacetic acid and sodium trimetaphosphate are performance-adjusting ingredients. The resulting collector is a water-soluble liquid agent with low-temperature resistance, easy dispersibility, and non-toxicity. The fluorine-free weak acid collector can be used for flotation in weakly acidic slurry environments with a pH of 3.5-5 without the need for other auxiliary reagents. It is suitable for various tailings containing feldspar and quartz, exhibiting excellent selective enrichment characteristics while reducing the risks of equipment corrosion and environmental pollution.
[0027] 2. In the fluorine-free weak acid collector of the present invention, the linear fatty alcohol in the collector acts as an active ingredient for collecting rather than enhancing foaming properties. It assists the electrostatic adsorption of quaternary ammonium salt through hydrogen bonding. The two are in equal proportions and are both major active ingredients, synergistically flotating on the feldspar surface. Chloroacetic acid in the collector acts as a solubilizer and stabilizer, while sodium trimetaphosphate is a component that enhances the selectivity of the collector, enabling it to float feldspar but not quartz. Therefore, the collector of the present invention has good water solubility, low-temperature resistance, easy dispersion, and is non-toxic. It can be adapted to the separation of quartz and feldspar in various tailings. The use of the collector does not require other auxiliary agents, nor does it require a strong acid environment or hydrofluoric acid activation, thus achieving green and comprehensive recovery of quartz and feldspar from tailings.
[0028] Other advantages, objectives and features of the present invention will become apparent in part from the following description, and in part from those skilled in the art through study and practice of the invention. Detailed Implementation
[0029] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0030] It should be noted that, unless otherwise specified, the experimental methods described in the following implementation plan are all conventional methods, and the reagents and materials described are all commercially available unless otherwise specified.
[0031] The fluorine-free weak acid collector of this invention represents a systematic innovation in the traditional feldspar-quartz flotation separation system. Traditional processes often rely on hydrofluoric acid (HF) activation or the use of amine collectors under strong acid conditions (pH<3). This not only places stringent requirements on equipment materials (requiring acid-resistant stainless steel or corrosion-resistant linings), but also results in extremely high costs for treating residual fluoride ions and strongly acidic wastewater, posing a significant burden on the environment.
[0032] This invention integrates four major functions—collection, inhibition, solubilization, and stabilization—into a single liquid reagent through the precise synergistic action of organic and inorganic multi-components, achieving highly efficient separation in weakly acidic (pH 3.5-5) slurry environments. The following is an in-depth technical extension on its component mechanisms of action and application advantages:
[0033] 1. The synergistic effect of the "dual active centers" in the core harvesting system (quaternary ammonium salt + straight-chain fatty alcohol)
[0034] Unlike the conventional physical mixture of "collector + foaming agent", the quaternary ammonium salt (cation) in this invention forms a stoichiometric synergistic adsorption pair with the straight-chain fatty alcohol.
[0035] Electrostatic anchoring of quaternary ammonium salts: In a weakly acidic environment of pH 3.5-5, the aluminum-oxygen tetrahedra on the feldspar surface become negatively charged due to protonation. Quaternary ammonium salt cations are oriented to adsorb onto the active sites on the feldspar surface through strong electrostatic attraction, thereby reducing its surface energy.
[0036] The dual "bridging-hydrophobic" function of fatty alcohols: The breakthrough of this invention lies in the fact that linear fatty alcohols do not act as traditional foaming agents (i.e., they do not dominate the stability of the bubble film), but rather directly participate in the construction of the crystal lattice. Their polar hydroxyl groups ( One end of the feldspar salt forms a supramolecular aggregate with the polar head group of the quaternary ammonium salt through intermolecular hydrogen bonds, while the long carbon chain alkyl group at the other end extends outward, greatly enhancing the thickness of the hydrophobic water film on the feldspar surface. The balanced ratio of these two components means that a mixed hemimicelle adsorption layer is formed on the feldspar surface. This co-adsorption mode has a higher adsorption density and stronger resistance to mud interference than that of a single quaternary ammonium salt, thus significantly improving the utilization efficiency of the collector.
[0037] 2. The "intramolecular lubrication" and pulp stabilizing effect of chloroacetic acid
[0038] In this formulation, chloroacetic acid acts as a "co-solvent" and "micelle stabilizer," rather than a collecting component.
[0039] Low-temperature solubility assurance: Quaternary ammonium salts and long-chain fatty alcohols are prone to stratification or crystallization at low temperatures (such as 5-10℃ in winter). The introduction of chloroacetic acid can insert into the barrier layer of surfactant micelles, reducing the micelle aggregation number, so that the agent can remain in a clear and homogeneous liquid state at room temperature or even low temperature, and can be added directly without heating and melting.
[0040] Metal ion concealment: Chloroacetic acid's weak chelating ability can preferentially complex metal ions that are inevitably present in the slurry. , The presence of polyvalent metal ions prevents these ions from being non-selectively adsorbed onto the quartz surface due to electrostatic neutralization, thereby avoiding the "accidental activation" of the quartz and indirectly improving the stability of the sorting environment.
[0041] 3. The "selective shielding" mechanism of sodium trimetaphosphate
[0042] As a selectivity enhancer, sodium trimetaphosphate (cyclic metaphosphate) is a "precision switch" that ensures the effective separation of feldspar and quartz:
[0043] In weakly acidic media, quartz surfaces mainly exist as siloxanes (≡Si-O-Si≡) and a small amount of silanol groups (≡Si-OH). The cyclic anions generated by the hydrolysis of sodium trimetaphosphate can preferentially and strongly adsorb onto the hydroxyl sites on the quartz surface through hydrogen bonding or coordination, forming a dense hydrophilic hydration film that effectively shields the electrostatic adsorption of quaternary ammonium cations on the quartz surface.
[0044] In contrast, the surface of feldspar The adsorption energy of the site for quaternary ammonium salt is much greater than the shielding energy of sodium trimetaphosphate. Therefore, the collector can only be effectively adsorbed on the feldspar surface, thus achieving highly selective separation of "floating feldspar and suppressing quartz".
[0045] 4. Process adaptability and green and low-carbon value
[0046] Simplified reagent formulation: Traditional processes require the addition of modifiers (sulfuric acid), activators (hydrofluoric acid), collectors, and frothers, and sometimes even require staged reagent addition. This invention achieves "one reagent for multiple uses," eliminating the need for pre-conditioning the pulp before flotation. Simply adjust the pH to the 3.5-5 range, and flotation can be completed with a single reagent addition, greatly reducing the complexity of on-site operations and labor costs.
[0047] The equipment is environmentally friendly: its operating pH value is close to neutral to slightly acidic, completely eliminating the high toxicity of hydrofluoric acid and the strong corrosiveness of strong acids. Ordinary carbon steel equipment can meet the requirements for long-term operation, eliminating the risk of heavy metal leaching caused by acid corrosion. Flotation tailings wastewater does not require expensive defluorination treatment; after simple neutralization and sedimentation, it can be recycled or discharged in compliance with standards, truly achieving green and comprehensive recovery of quartz and feldspar from tailings without fluorine, acid, or auxiliary reagents.
[0048] Wide adaptability to raw materials: Since this reagent system does not depend on a specific mineral lattice constant, whether it is a feldspar-quartz symbiotic system in granite sawdust, lepidolite tailings or iron tailings, this collector can effectively cope with the flotation fluctuations caused by differences in surface oxidation or lattice impurities in ores from different origins by virtue of its stable selective adsorption mechanism.
[0049] Example 1
[0050] A fluorine-free weak acid collector comprises the following components in parts by weight:
[0051] Four parts of a quaternary ammonium salt with a carbon chain length of C12, six parts of a straight-chain fatty alcohol with a carbon chain length of C10, one part of chloroacetic acid, eight parts of sodium trimetaphosphate, and eight parts of deionized water.
[0052] The preparation method of the above-mentioned fluorine-free weak acid collector includes the following steps:
[0053] S1. Mix 4 parts by weight of a quaternary ammonium salt with a carbon chain length of C12 and 6 parts by weight of a straight-chain fatty alcohol with a carbon chain length of C10, and then heat to 60°C.
[0054] S2. After the mixture obtained in S1 has melted, add 1 part by weight of chloroacetic acid and 8 parts by weight of deionized water to it, and stir and react at 60°C for 50 min.
[0055] S3. After the mixture obtained in S2 has reacted completely, add 8 parts by weight of sodium trimetaphosphate and mix well to obtain the collector stock solution.
[0056] S4. Add deionized water to dilute the collector stock solution obtained in S3 to obtain the fluorine-free weak acid collector, wherein the concentration of the collector stock solution in the diluted fluorine-free weak acid collector is 2%.
[0057] Example 2
[0058] A fluorine-free weak acid collector comprises the following components in parts by weight:
[0059] Five parts of a quaternary ammonium salt with a carbon chain length of C12, five parts of a straight-chain fatty alcohol with a carbon chain length of C12, two parts of chloroacetic acid, ten parts of sodium trimetaphosphate, and fourteen parts of deionized water.
[0060] The preparation method of the above-mentioned fluorine-free weak acid collector includes the following steps:
[0061] S1. Mix 5 parts by weight of a quaternary ammonium salt with a carbon chain length of C12 and 5 parts by weight of a straight-chain fatty alcohol with a carbon chain length of C12, and then heat to 65°C.
[0062] S2. After the mixture obtained in S1 has melted, add 1 part by weight of chloroacetic acid and 8 parts by weight of deionized water to it, and stir and react at 65°C for 50 min.
[0063] S3. After the mixture obtained in S2 has reacted completely, add 10 parts by weight of sodium trimetaphosphate and mix well to obtain the collector stock solution.
[0064] S4. Add deionized water to dilute the collector stock solution obtained in S3 to obtain the fluorine-free weak acid collector, wherein the concentration of the collector stock solution in the diluted fluorine-free weak acid collector is 2%.
[0065] Example 3
[0066] A feldspar-quartz flotation separation method is used, employing the fluorine-free weak acid collector obtained in Example 1 above. The tailings used are tailings from lithium mica after lithium beneficiation in Jiangxi Province. The mineral content of feldspar and quartz in the tailings is 97%, and the composition is shown in Table 1 (weight percentage).
[0067] Table 1. Multi-element chemical analysis
[0068]
[0069] Specifically, the above-mentioned feldspar-quartz flotation separation method includes the following steps:
[0070] Step 1: Grind the above tailings until the proportion of particles smaller than 0.074mm is 40%, and then add water to adjust to obtain a slurry with a mass concentration of 35%.
[0071] Step 2: Add 1% hydrochloric acid or sulfuric acid to the slurry obtained in Step 1 to adjust its pH to 3.5;
[0072] Step 3: Using the fluorine-free weak acid collector, add it to the slurry treated in Step 2 for flotation roughing to obtain frothy product and underflow product. The flotation temperature is 15-40℃, and the collector consumption during flotation roughing is 1800g / t.
[0073] Step 4: Using the aforementioned fluorine-free weak acid collector, perform three flotation cleaning processes on the underflow product obtained in Step 3. Maintain the pulp pH at 3.5 during the flotation cleaning process, with each flotation cleaning session lasting 2-3 minutes. The froth product generated during flotation cleaning is mixed with the froth product obtained in Step 3. Specifically, the collector consumption during the first flotation cleaning is 50% of the collector consumption during the roughing stage in Step 3, and the collector consumption during each subsequent flotation cleaning is 50% of the collector consumption during the previous flotation cleaning.
[0074] Step 5: Filter and dry the underflow product after flotation and the final foam product separately to obtain quartz product and feldspar product respectively.
[0075] Example 4
[0076] A feldspar-quartz flotation separation method is used, employing the fluorine-free weak acid collector obtained in Example 1 above, and using the same tailings as those used in Example 3.
[0077] Specifically, the above-mentioned feldspar-quartz flotation separation method includes the following steps:
[0078] Step 1: Grind the above tailings until the proportion of particles smaller than 0.074mm is 40%, and then add water to adjust to obtain a slurry with a mass concentration of 35%.
[0079] Step 2: Add 1% hydrochloric acid or sulfuric acid to the slurry obtained in Step 1 to adjust its pH to 3.5;
[0080] Step 3: Using the fluorine-free weak acid collector, add it to the slurry treated in Step 2 for flotation roughing to obtain frothy product and underflow product. The flotation temperature is 15-40℃, and the collector consumption during flotation roughing is 1800g / t.
[0081] Step 4: Using the aforementioned fluorine-free weak acid collector, perform four flotation cleaning processes on the underflow product obtained in Step 3. Maintain the pulp pH at 3.5 during the flotation cleaning process, with each flotation cleaning session lasting 2-3 minutes. The froth product generated during flotation cleaning is mixed with the froth product obtained in Step 3. Specifically, the collector consumption during the first flotation cleaning is 50% of the collector consumption during the roughing stage in Step 3, and the collector consumption during each subsequent flotation cleaning is 50% of the collector consumption during the previous flotation cleaning.
[0082] Step 5: Filter and dry the underflow product after flotation and the final foam product separately to obtain quartz product and feldspar product respectively.
[0083] Example 5
[0084] A feldspar-quartz flotation separation method is used, employing the fluorine-free weak acid collector obtained in Example 1 above, and using the same tailings as those used in Example 3;
[0085] Specifically, the above-mentioned feldspar-quartz flotation separation method includes the following steps:
[0086] Step 1: Grind the above tailings until the proportion of particles smaller than 0.074mm is 50%, and then add water to adjust to obtain a slurry with a mass concentration of 35%.
[0087] Step 2: Add 1% hydrochloric acid or sulfuric acid to the slurry obtained in Step 1 to adjust its pH to 3.5;
[0088] Step 3: Using the fluorine-free weak acid collector, add it to the slurry treated in Step 2 for flotation roughing to obtain frothy product and underflow product. The flotation temperature is 15-40℃, and the collector consumption during flotation roughing is 1800g / t.
[0089] Step 4: Using the aforementioned fluorine-free weak acid collector, perform three flotation cleaning processes on the underflow product obtained in Step 3. Maintain the pulp pH at 3.5 during the flotation cleaning process, with each flotation cleaning session lasting 2-3 minutes. The froth product generated during flotation cleaning is mixed with the froth product obtained in Step 3. Specifically, the collector consumption during the first flotation cleaning is 50% of the collector consumption during the roughing stage in Step 3, and the collector consumption during each subsequent flotation cleaning is 50% of the collector consumption during the previous flotation cleaning.
[0090] Step 5: Filter and dry the underflow product after flotation and the final foam product separately to obtain quartz product and feldspar product respectively.
[0091] Example 6
[0092] A feldspar-quartz flotation separation method is used, employing the fluorine-free weak acid collector obtained in Example 2 above, and using the same tailings as in Example 3;
[0093] Specifically, the above-mentioned feldspar-quartz flotation separation method includes the following steps:
[0094] Step 1: Grind the above tailings until the proportion of particles smaller than 0.074mm is 40%, and then add water to adjust to obtain a slurry with a mass concentration of 35%.
[0095] Step 2: Add 1% hydrochloric acid or sulfuric acid to the slurry obtained in Step 1 to adjust its pH to 3.5;
[0096] Step 3: Using the fluorine-free weak acid collector, add it to the slurry treated in Step 2 for flotation roughing to obtain frothy product and underflow product. The flotation temperature is 15-40℃, and the collector consumption during flotation roughing is 2500g / t.
[0097] Step 4: Using the aforementioned fluorine-free weak acid collector, perform three flotation cleaning processes on the underflow product obtained in Step 3. Maintain the pulp pH at 3.5 during the flotation cleaning process, with each flotation cleaning session lasting 2-3 minutes. The froth product generated during flotation cleaning is mixed with the froth product obtained in Step 3. Specifically, the collector consumption during the first flotation cleaning is 50% of the collector consumption during the roughing stage in Step 3, and the collector consumption during each subsequent flotation cleaning is 50% of the collector consumption during the previous flotation cleaning.
[0098] Step 5: Filter and dry the underflow product after flotation and the final foam product separately to obtain quartz product and feldspar product respectively.
[0099] Example 7
[0100] A feldspar-quartz flotation separation method is used, employing the fluorine-free weak acid collector obtained in Example 2 above, and using the same tailings as in Example 3;
[0101] Specifically, the above-mentioned feldspar-quartz flotation separation method includes the following steps:
[0102] Step 1: Grind the above tailings until the proportion of particles smaller than 0.074mm is 50%, and then add water to adjust to obtain a slurry with a mass concentration of 35%.
[0103] Step 2: Add 1% hydrochloric acid or sulfuric acid to the slurry obtained in Step 1 to adjust its pH to 3.5;
[0104] Step 3: Using the fluorine-free weak acid collector, add it to the slurry treated in Step 2 for flotation roughing to obtain frothy product and underflow product. The flotation temperature is 15-40℃, and the collector consumption during flotation roughing is 2500g / t.
[0105] Step 4: Using the aforementioned fluorine-free weak acid collector, perform 5 flotation cleaning processes on the underflow product obtained in Step 3. Maintain the pulp pH at 3.5 during the flotation cleaning process, with each flotation cleaning session lasting 2-3 minutes. The froth product generated during the flotation cleaning process is mixed with the froth product obtained in Step 3. Specifically, the collector consumption during the first flotation cleaning process is 50% of the collector consumption during the roughing flotation in Step 3, and the collector consumption during each subsequent flotation cleaning process is 50% of the collector consumption during the previous flotation cleaning process.
[0106] Step 5: Filter and dry the underflow product after flotation and the final foam product separately to obtain quartz product and feldspar product respectively.
[0107] Data Analysis
[0108] The quartz and feldspar products obtained in Examples 3-7 were tested for the Na2O+K2O content in the feldspar product and the Si2O content in the quartz product, respectively. The test results are shown in Table 2 below.
[0109] Table 2 Test Results
[0110]
[0111] According to the test results in Table 1:
[0112] Comparing Examples 3 and 4, it can be seen that increasing the number of cleaning cycles can improve the flotation separation effect of the collector on quartz and feldspar; comparing Examples 3 and 5, it can be seen that increasing the grinding fineness is beneficial to the flotation separation of quartz and feldspar; comprehensively comparing Examples 3, 6 and 7, it can be seen that simultaneously increasing the grinding fineness, the number of cleaning cycles and the amount of collector can significantly improve the flotation separation effect of quartz and feldspar, and can obtain feldspar products and quartz products that meet the first-grade feldspar standard and industrial high-purity quartz sand grade.
[0113] Although embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and embodiments. They can be applied to various fields suitable for the present invention. For those skilled in the art, other modifications can be easily made. Therefore, without departing from the general concept defined by the claims and their equivalents, the present invention is not limited to the specific details and embodiments shown and described herein.
Claims
1. A fluorine-free weak acid collector, characterized in that, The components include the following parts by weight: 3-7 parts quaternary ammonium salt, 3-7 parts linear fatty alcohol, 1-3 parts chloroacetic acid, 6-14 parts sodium trimetaphosphate, and 8-20 parts deionized water.
2. The fluorine-free weak acid collector as described in claim 1, characterized in that, The carbon chain length of the quaternary ammonium salt is C10-C18.
3. The fluorine-free weak acid collector as described in claim 1, characterized in that, The carbon chain length of the straight-chain fatty alcohol is C8-C12.
4. A method for preparing a fluorine-free weak acid collector as described in any one of claims 1-3, characterized in that, Includes the following steps: S1. Mix 3-7 parts by weight of quaternary ammonium salt and 3-7 parts by weight of straight-chain fatty alcohol, and then heat to 50-70℃; S2. After the mixture obtained in S1 has melted, add 1-3 parts by weight of chloroacetic acid and 8-20 parts by weight of deionized water, and stir the mixture at 50-70°C for 30-60 minutes. S3. After the mixture obtained in S2 has reacted completely, add 6-14 parts by weight of sodium trimetaphosphate and mix well to obtain the collector stock solution. S4. Add deionized water to dilute the collector stock solution obtained in S3 to obtain the fluorine-free weak acid collector.
5. The method for preparing the fluorine-free weak acid collector as described in claim 4, characterized in that, In the diluted non-fluorine weak acid collector in S4, the concentration of the original collector solution is 2-10%.
6. A feldspar-quartz flotation separation method, characterized in that, The fluorine-free weak acid collector described in any one of claims 1-3 is used.
7. The feldspar-quartz flotation separation method as described in claim 4, characterized in that, Includes the following steps: Step 1: Take tailings with a quartz and feldspar mineral content of more than 95%, grind them until the proportion of particles with a particle size of less than 0.074mm is 40-90%, and then add water to adjust to obtain a slurry with a mass concentration of 25-40%. Step 2: Add hydrochloric acid or sulfuric acid to the slurry obtained in Step 1 to adjust its pH to 3.5-5; Step 3: Using the fluorine-free weak acid collector, add it to the slurry treated in Step 2 for flotation roughing to obtain froth product and underflow product. The flotation temperature is 15-40℃. Step 4: Using the fluorine-free weak acid collector, the underflow product obtained in Step 3 is subjected to multiple flotation cleaning processes. The pH of the pulp is maintained at 3.5-5 during the flotation cleaning process, and the time for each flotation cleaning is 2-3 minutes. The froth product generated by the flotation cleaning is mixed into the froth product obtained in Step 3. Step 5: Filter and dry the underflow product after flotation and the final foam product separately to obtain quartz product and feldspar product respectively.
8. The feldspar-quartz flotation separation method as described in claim 7, characterized in that, The tailings in step one are one or any combination of lithium mica tailings, iron ore tailings, copper ore tailings and phosphate ore tailings.
9. The feldspar-quartz flotation separation method as described in claim 7, characterized in that, In step four, the collector consumption during the first flotation cleaning is 50% of the collector consumption during the flotation roughing in step three, and the collector consumption during each subsequent flotation cleaning is 50% of the collector consumption during the previous flotation cleaning.
10. The feldspar-quartz flotation separation method as described in claim 7, characterized in that, In step three, the collector consumption during the roughing flotation is 1000-3000 g / t.